REPRESENTASI TINDAK TUTUR DIREKTIF BAHASA INDONESIA SISWA KELAS XI SMA NEGERI 15 PADANG - Larassaty, Suci; R., Syahrul; Gani, Erizal (Universitas Negeri Padang, 2016)
ABSTRACTÂ The aim of this study was to describe the shape, strategy and context of directive speech acts of Bahasa Indonesia at eleventh grade students in SMA N 15 Padang. The type of this research is qualitative research by using descriptive methods. The source of the data on the research of directive speech acts of Bahasa Indonesia is eleventh grade students of SMAN 15 Padang. The findings of this research is directive speech acts of Bahasa Indonesia as a speech act that has great chance to used during the discussion process that there were 106 utterances. Demanding speech acts have become a kind of speech act that is most often used with a percentage of 75.5%. Discussions strategy which is dominant use is a strategy speak frankly without further positive politeness to the context of formal speech acts as the background activity of the students in the classroom discussion.Â Kata kunci: Direktif, Strategi, Konteks